Salivary Microbiome in Pediatric and Adult Celiac Disease - Dimitri Poddighe; Аlmagul Kushugulova (Frontiers Media SA, 2021)
The human salivary microbiota includes hundreds of bacterial species. Alterations in gut microbiota have been explored in Celiac Disease (CD), but fewer studies investigated the characteristics of salivary microbiome in these patients, despite the potential implications in its pathogenesis. Indeed, some recent studies suggested that the partial digestion of gluten proteins by some bacteria may affect the array of gluten peptides reaching the gut and the way by which those are presented to the intestinal immune system. The available clinical studies investigating the salivary microbiota in children and adults, are insufficient to make any reliable conclusion, even though some bacterial species/phyla differences have been reported between celiac patients and controls. However, the salivary microbiome could correlate better with the duodenal microbiota, than the fecal one. Therefore, further clinical studies on salivary microbiome by different and independent research groups and including different populations, are advisable in order to explore the usefulness of the salivary microbiome analysis and understand some aspects of CD pathogenesis with potential clinical and practical implications.
Keywords: Microbiome; Pathogenesis; Saliva; Immunology; Disease; Biology; Immune system; Human microbiome; Medicine; Bioinformatics; Pathology; Biochemistry; type of access: open access